2022
DOI: 10.2196/33909
|View full text |Cite
|
Sign up to set email alerts
|

Examining Public Sentiments and Attitudes Toward COVID-19 Vaccination: Infoveillance Study Using Twitter Posts

Abstract: Background A global rollout of vaccinations is currently underway to mitigate and protect people from the COVID-19 pandemic. Several individuals have been using social media platforms such as Twitter as an outlet to express their feelings, concerns, and opinions about COVID-19 vaccines and vaccination programs. This study examined COVID-19 vaccine–related tweets from January 1, 2020, to April 30, 2021, to uncover the topics, themes, and variations in sentiments of public Twitter users. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 44 publications
1
20
0
3
Order By: Relevance
“…Fourth, this study adopted content analysis and did not incorporate the effects of images or emoticons. In a literature review, we found that researchers removed emojis during preprocessing and cleaning of vaccine message text data to study multiple topics in Twitter, such as online vaccination debates [ 73 ], childhood vaccination opinions [ 74 ], COVID-19 vaccine sentiment in the United States [ 75 ], and key themes and topics on COVID-19 vaccines [ 76 ]. On similar lines of the literature, we removed emojis from the Twitter text corpus to analyze our dissemination model.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, this study adopted content analysis and did not incorporate the effects of images or emoticons. In a literature review, we found that researchers removed emojis during preprocessing and cleaning of vaccine message text data to study multiple topics in Twitter, such as online vaccination debates [ 73 ], childhood vaccination opinions [ 74 ], COVID-19 vaccine sentiment in the United States [ 75 ], and key themes and topics on COVID-19 vaccines [ 76 ]. On similar lines of the literature, we removed emojis from the Twitter text corpus to analyze our dissemination model.…”
Section: Discussionmentioning
confidence: 99%
“…Ada beragam cara untuk melakukan ekstraksi data cuitan twitter, tentunya dengan kelebihan dan kekurangan masingmasing [10]. Dari twitter API [11], tweepy, TWINT, dan snscrape [5], penulis memilih snscrape yang berbasis bahasa python untuk melakukan ekstraksi data cuitan twitter. Penulis melakukan ekstraksi data cuitan twitter berdasarkan dua durasi waktu, yaitu sebelum Muhaimin Iskandar melontarkan isu (1 Januari 2022 sampai dengan 23 Februari 2022) dan setelah Muhaimin Iskandar melontarkan isu (24 Februari 2022 sampai dengan 27 Mei 2022).…”
Section: A Ekstraksi Data Cuitan Twitterunclassified
“…Analisis sentimen terhadap data twitter juga pernah dilakukan untuk melihat sentimen masyarakat di era COVID 19, di antaranya menilai sentimen masyarakat dengan menggunakan VADER (Valence Aware Dictionary and Sentiment Reasoner) terhadap program vaksinasi [5][6] atau bahkan sentimen masyarakat pada saat wabah COVID 19 sedang meninggi [7].…”
unclassified
“…The unprecedented speed of messenger RNA vaccine development and approval has raised concerns that clinical trials were hastened and regulatory standards were relaxed [ 9 ]. Several recent topic modeling studies have reported concerns about AEs as a common major topic [ 10 - 13 ]. Moreover, most countries have used various vaccine brands (eg, Moderna, Pfizer, AstraZeneca, and Jassen), each with different use guidelines and safety and efficacy profiles [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We reviewed a rich body of existing literature on topics and sentiments related to COVID-19 vaccines using social media data ( Multimedia Appendix 1 [ 4 - 8 , 10 - 13 , 17 - 30 ]). The major data source was Twitter (21 studies), and other sources were Reddit (2 studies), Facebook (1 study), and Weibo (1 study).…”
Section: Introductionmentioning
confidence: 99%